Promotion effect and mechanism of the addition of Mo on the enhanced low temperature SCR of NOx by NH3 over MnOx/γ-Al2O3 catalysts - Yang, Gang; Zhao, Haitao; Luo, Xiang; Shi, Kaiqi; Zhao, Haibao; Wang, Wenkai; Chen, Quhan; Fan, Hua; Wu, Tao (2019)
A series of Mn/γ-Al2O3 and MnMo/γ-Al2O3 catalysts were prepared by using Incipient Wetness Impregnation (IWI) method. The catalytic performance tests showed that the Mn3Mo1.25/γ-Al2O3 demonstrated a higher SCR performance (NO conversion of around 96%) at a broad low temperature range (150 to 300°C). The characterization showed that the addition of Mo to the Mn/γ-Al2O3 catalysts could promote the dispersion of MnOx on the surface of γ-Al2O3. The adsorption of NO could form two different species, nitrites and nitrates on the surface of the catalyst. The presence of nitrites is beneficial to low temperature SCR. It is also found that the existence of Mo in the catalyst favours the formation of Mn3+, which plays a critical role in the adsorption of NH3 and therefore improves NH3 adsorption capacity of the MnOx/γ-Al2O3 catalysts. The low temperature SCR of the Mn3Mo1.25/γ-Al2O3 catalyst was found to mainly follow L-H mechanism, but E-R mechanism also plays a role to some extent. Moreover, it is also found that the addition of Mo not only mitigates the deactivation of catalysts, but also broadens the effective temperature range of the SCR catalyst.